Characteristics of semen collection floors and effect on sexual behaviour and semen quality of Murrah bulls - AP Singh; Rajbir Singh; A Singh; AK Gupta; VS Raina; AK Chakravarty (Journal of Livestock Biodiversity, 2025)
The present study was carried out on Murrah breeding bulls maintained at artificial breeding complex of NDRI,Karnal and JV Degree College, Baraut, Baghpat. The investigation was aimed to assess the reproductive activity ofMurrah bulls on the basis of sexual behaviour characters and seminal attributes as a result of introduction ofmanagement interventions. To study the effect of collection floor, three types of semen collection floors viz.,concrete floor, brick clay floor and rubber mattress were provided. Data recorded on sexual behaviour and seminalattributes were statistically analyzed. The results indicated that bulls were very active and had higher sexualstimulation before semen collection on rubber mattress followed by brick clay floor and concrete collection floor asreflected by reaction time, dismounting time, total time taken in mounts and other behavioural manifestations.Erection score, protrusion score, intensity of thrust, temperament score and libido score were highly influenced bythe type of floor. Analysis of seminal attributes revealed highly significant variation in ejaculate volume betweenbulls exposed to different types of collection floor. Rubber mattress showed significantly higher value of semenvolume which confirmed its superiority in semen collection over other types of floors. However, physicalappearance, mass activity, initial progressive motility, non eosinophilic spermatozoa count, post thaw motility,hypo osmotic swelling test were not significantly affected by the type of floor. Thus the rubber mattress collectionflooring helps in improving the semen output without having any detrimental effect on semen quality.